Improving patient specific quality assurance for image registration: clinical use case of target contouring for PET deformable image registration - Johnson Yuen; Joel Poder; Michael Jameson; Laurel Schmidt; Ryan Brown; Charlotte Atkinson; Shrikant Deshpande; Anna Ralston; Lois Holloway (Physical and Engineering Sciences in Medicine, 2025)
Deformable image registration (DIR) has proven to be an invaluable tool to maximize the clinical benefits of multimodality imaging in radiation oncology. In contrast to rigid image registration (RIR), which is employed at all stages of diagnosis and treatment, the uptake of DIR has been constrained by concerns over the potential for unsafe use. The AAPM Task Group 132 (TG132) published a report on the use of image registration, including many recommendations on clinical integration of registration in treatment planning and delivery. There is a remaining uncertainty on incorporating registration uncertainties into treatment margins (Sect. 6.A, TG 132), a challenge in clinical practice. The aim of this work was to report our experience in implementing a practical, patient specific quality assurance process based on the AAPM Task Group 132 report recommendations. This work includes refining our process of target contouring using PET with deformable image registration based on our experience of addressing vulnerabilities identified during implementation. A multidisciplinary team created a flowchart for patient specific quality assurance for image registration (RIR or DIR) based on use cases defined in the AAPM TG132 Report on the use of image registration in radiotherapy. Vulnerabilities identified from this implementation were assessed relative to AAPM TG132 recommendations. These findings were used to adapt our patient specific quality assurance to mitigate vulnerabilities. The main vulnerabilities were identified in the last steps of image registration. There was potential for inappropriate use of the registration for clinical use, such as target contouring where the image registration accuracy level was poor. Vulnerabilities were addressed by an adaptation in our quality assurance process. A new physics image registration QA task was introduced that independently checks registration accuracy and appropriateness of target contouring, addressing the vulnerability in the last steps of the AAPM TG132 flowchart. A multi-disciplinary team implemented the image registration process outlined by AAPM TG132. An improved patient specific quality assurance process was developed by introducing an independent physics image registration review that considers the acceptable registration uncertainty for the specific clinical use case in question.

Current status of intra-cranial stereotactic radiotherapy and stereotactic radiosurgery in Australia and New Zealand: key considerations from a workshop and surveys - Lauren Pudsey; Annette Haworth; Paul White; Zoe Moutrie; Benjamin Jonker; Matthew Foote; Joel Poder (Physical and Engineering Sciences in Medicine, 2022)
Recently, there has been increased interest worldwide in the use of conventional linear accelerator (linac)-based systems for delivery of stereotactic radiosurgery/radiotherapy (SRS/SRT) contrasting with historical delivery in specialised clinics with dedicated equipment. In order to gain an understanding and define the current status of SRS/SRT delivery in Australia and New Zealand (ANZ) we conducted surveys and provided a single-day workshop. Prior to the workshop ANZ medical physicists were invited to complete two surveys: a departmental survey regarding SRS/SRT practises and equipment; and an individual survey regarding opinions on current and future SRS/SRT practices. At the workshop conclusion, attendees completed a second opinion-based survey. Workshop discussion and survey data were utilised to identify areas of consensus, and areas where a community consensus was unclear. The workshop was held on the 8th Sept 2020 virtually due to pandemic-related travel restrictions and was attended by 238 radiation oncology medical physicists from 39 departments. The departmental survey received 32 responses; a further 89 and 142 responses were received to the pre-workshop and post-workshop surveys respectively. Workshop discussion indicated a consensus that for a department to offer an SRS/SRT service, a minimum case load should be considered depending on availability of training, peer-review, resources and equipment. It was suggested this service may be limited to brain metastases only, with less common indications reserved for departments with comprehensive SRS/SRT programs. Whilst most centres showed consensus with treatment delivery techniques and image guidance, opinions varied on the minimum target diameter and treatment margin that should be applied.